Multi-stakeholder partnerships for the inclusion of farmers in the value chain: the case of vanilla in Madagascar - Mamitiana, Fanjaniaina Prisca (2016)
Since the World Summit in Johannesburg in 2002, the role of private sector in development has been acknowledged, and partnerships have been formalised as important means toward it. This study aims to examine the partnerships and partnerships governance mechanisms established by companies sourcing vanilla in Madagascar for integrating low-income farmers in their value chain. The central question that this research aims to answer is: how do multi-stakeholder partnerships established by businesses promote the integration of farmers in the value chain? To answer this question, a methodology based on three case studies of three large companies sourcing their vanilla in the North part of Madagascar and a content analysis performed on the translated transcripts of interviews of managers from these businesses. It has been found that producing good quality of vanilla is the primary condition for farmers to be included in the value chain. For that, companies work with business and non-business actors to provide technical supports based on materials and agricultural expertise assistance. Also, they are engaging in a different form of Corporate Social Responsibility activities to allow farmers to produce the required quality of vanilla. Formal and informal mechanisms are used to govern these partnerships, but governance mechanisms with farmers are only based on trust.